A set of abilities that make up the activity of a tutor. - Nurmatova Madina Odiljan Qizi (Periodica Journal, 2024)
This article presents a discussion about the abilities of a tutor. The role of the tutor's ability in his work is expressed. The overall success of a tutor, the ability to influence students in the educational system is evaluated as a systematic process that depends on his abilities.
Keywords: Tutor; ability; tutor